2019
DOI: 10.1126/sciadv.aav3208
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immunity and antibodies to dengue virus promote infection and Zika virus–induced microcephaly in fetuses

Abstract: Zika virus (ZIKV), an emergent flaviviral pathogen, has been linked to microcephaly in neonates. Although the risk is greatest during the first trimester of pregnancy in humans, timing alone cannot explain why maternal ZIKV infection leads to severe microcephaly in some fetuses, but not others. The antigenic similarities between ZIKV and dengue virus (DENV), combined with high levels of DENV immunity among ZIKV target populations in recent outbreaks, suggest that anti-DENV maternal antibodies could promote ZIK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 58 publications
9
100
0
Order By: Relevance
“…Recently, it was suggested that fetal genetic background could predispose to malformation development after ZIKV vertical transmission (8). Beyond genetic predisposition, it was shown that environmental factors, such as the previous exposure to dengue virus, increase susceptibility to ZIKV congenital infection and lead to more exacerbated phenotypic alterations in the brain (24). Since immune status also depends on nutritional conditions, these are crucial elements to understand differential infection outcomes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that fetal genetic background could predispose to malformation development after ZIKV vertical transmission (8). Beyond genetic predisposition, it was shown that environmental factors, such as the previous exposure to dengue virus, increase susceptibility to ZIKV congenital infection and lead to more exacerbated phenotypic alterations in the brain (24). Since immune status also depends on nutritional conditions, these are crucial elements to understand differential infection outcomes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Dengue virus re-infection can lead to antibodyenhanced disease by a mechanism that is associated with serologic cross-reactivity between different dengue serotypes (40)(41)(42). Antibodies to dengue also cross-react with ZIKV and experiments in mice and with human placental explants have shown that ZIKV infection can be enhanced by antibodies in these systems (43)(44)(45)(46). Conversely, antibodies to ZIKV that are maternally acquired cause more severe disease in mice infected with dengue (47).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies in immune compromised mice have suggested that DENV T cell immunity can be protective against ZIKV infection in adult mice (24), other studies in STAT2-KO mice, with impaired immunity, showed prior DENV immunity can enhance infection in adult mice and infection and fetal demise in pregnant mice (25,26). In immune competent mice, preexisting DENV immunity can enhance the development of a microcephaly phenotype in fetuses (27,28), which is a key characteristic pathology of disease. These studies suggest that various factors determine cross-protection, some of which are discussed below.…”
Section: Functional Immune Outcomes Of Sequential Flavivirus Infectionsmentioning
confidence: 99%
“…As discussed, despite this high cross-reactivity, DENV-specific antibodies fail to cross-neutralize ZIKV (12), but may lead to opsonization of ZIKV viral particles (65). Not only was this shown to occur in conventional antigen presenting cells, dependent on the Fc gamma receptors, DENV antibodies can also enhance uptake of ZIKV in the syncytiotrophoblasts, and fetal endothelial cells of the placenta in a mechanism dependent on the fetal neonatal Fc Receptor, FcRN (27). In support of the role of antibody dependent enhancement of ZIKV pathology in vivo in humans, mothers with antibodies that were highly enhancing to ZIKV were shown to have fetuses (or children) with more severe microcephaly phenotypes (68).…”
Section: Flavivirus Cross-reactive Antibody Responsesmentioning
confidence: 99%